SERVANT LEADERSHIP AND ITS INFLUENCE ON EMPLOYEE PERFORMANCE - Silalahi, Marto; Candra, Vivi; Grace, Ernest; Simatupang, Sudung; Julyanthry, Julyanthry (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Servant leadership is currently emerging as a modern leadership style that is expected to produce good performance for the organization. The purpose of this study was conducted to determine whether service leadership is able to affect employee performance, the results of the study found that servant leadership has a positive and significant coefficient on performance, it is shown through the results of the equation Y = 7.610 + 0.492 X, then the results of the hypothesis show that service leadership has a positive and significant effect on performance. This means that leaders who are able to serve as servants for their members will be able to provide positive results on the performance of their members, and if leaders can become servants directly, they will create high loyalty for their members and reduce turnover rates for the organization.